Radiation thermal processes in Cr13Mo2NbVB steel - the material of the fuel assembly shell in reactor BN-350 under mechanical tests; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Larionov A. S.; Dikov А. S.; Poltavtseva V. P.; Kislitsin S. B.; Kuimova M. V. Marina Valerievna; Chernyavski (Chernyavskiy) A. V. Aleksandr Viktorovich (2015, 2015)
Title screen